Pembuatan KIT Sederhana Rangkaian Listrik Dinamis Sebagai Produk Akhir Pada Mata Kuliah Praktikum IPA - Rizaldi, Dedi Riyan; Harwati, Kasmah; Fatimah, Ziadatul; Makhrus, Muh. (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2020)
Learning physics is of course a part of science and should be able to facilitate students to do lab sessions or experiments to prove the concepts learned. One of them relates to dynamic electricity at the secondary level. However, there are still many schools that do not have practical tools that can assist students in learning dynamic electricity equipment. Therefore, the writing of this article is to explain the process of making a simple KIT dynamic electrical circuit as the final product in the science practicum course. The process to create this KIT consists of three stages, namely preparation, implementation and testing. Based on the work carried out, this appears 1). The process of making a dynamic electrical circuit KIT is divided into two parts, namely making tool sets and storage boxes, and 2). Practical activities that can use this electrical circuit KIT include measuring the size of GGL on the battery, measuring the voltage and electrical current, as well as series and parallel circuits